1996
DOI: 10.1159/000211412
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Expression of Steroidogenesis Enzyme Subtypes in the Human Pilosebaceous Unit

Abstract: In order to define the respective involvement of steroidogenesis enzymes subtypes in the control of hair follicle homeostasis, we evaluated, by semiquantitative RT/PCR, the expression levels of mRNAs coding for 17 β-hydroxysteroid dehydrogenase type 1 and type 2, 3β-hydroxysteroid dehydrogenase, Cyt.P450-aromatase, steroid 5α-reductase type 1 and type 2 and 11 β-hydroxysteroid dehydrogenase. These assays were performed for several components of the pilosebaceous unit (PSU); fresh plucked anagen hairs, sebaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 20 publications
4
27
0
1
Order By: Relevance
“…Other studies have demonstrated similar results, even when SDR5A1 mRNA was investigated in cultured follicular keratinocytes (24,33). Plucked anagen hairs are mainly constituted by keratinocyte cells forming both outer and inner root sheaths.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Other studies have demonstrated similar results, even when SDR5A1 mRNA was investigated in cultured follicular keratinocytes (24,33). Plucked anagen hairs are mainly constituted by keratinocyte cells forming both outer and inner root sheaths.…”
Section: Discussionsupporting
confidence: 64%
“…Some immunohistochemical and enzyme activity studies have suggested a predominant expression of SDR5A1 enzyme in sebaceous glands, but also in sweat glands, epidermal cells, root sheath and dermal papilla cells from hair follicles (19)(20)(21), whereas SDR5A2 is only expressed in these compartments at very low levels. In contrast, other studies have demonstrated a different distribution of these isoenzymes inside the pilosebaceous unit (22)(23)(24). There seems to be a higher distribution of SDR5A1 in hair follicle compartments compared to SDR5A2.…”
Section: Introductionmentioning
confidence: 55%
“…Since dihydrotestosterone, a well-known negative signal for scalp hair growth, is produced in hair follicles from testosterone through the action of 5a-reductase(s) [18] and since we [ 12] and others [ 19,20] reported the presence of 5a-reductase isozymes in the human scalp pilosebaceous unit, it is likely that these en zymes and other steroidogenesis enzymes [ 12] might be, to some extent, transcriptionally upregulated by IL-la. This remains however to be established.…”
Section: Discussionmentioning
confidence: 87%
“…isolated hair follicles have been reported to elongate for over a period of 15-30 days in culture [6,11]. In addition, we have shown that plucked hair follicles could restitute an instantaneous picture of mRNA status in the ORS of the hair follicle [12]. We therefore have taken advantage of these two methods to (i) better define the inflammatory cytokine/ IL-1 receptor niRNA status in the ORS of freshly plucked human anagen hair follicles, (ii) confirm the inhibitory effects of IL-1 on hair growth in vitro, (iii) evaluate the reper toire of inflammatory cytokines/IL-1 actually expressed in freshly plucked human anagen hair follicles using the reverse transcriptase polymerase chain reaction (RT/PCR), (iv) de sign a simple and reliable assay that might be helpful for the clinician to adapt a proper therapy to the inflammatory alopecic patient.…”
Section: Inflammatory Cytokines In Hair Folliclementioning
confidence: 85%
“…11-hydroxysteroids [27] or other hydroxysteroids as observed by studies of androgen metabolism in the liver [28]. Radioactivity at the origin (R f value 0-0.05) ranging from 0 to 3% of total radioactivity may be due to androsterone glucuronides or sulfates since solvent extraction from the media amounts to 90-95%.…”
Section: Discussionmentioning
confidence: 99%